PENGARUH INTENSITAS CURAH HUJAN TERHADAP PENDAPATAN PETANI - Nadia Ahsan (PRIMA EKSAKTA, 2026)
This study aims to analyze the effect of rainfall intensity on the net income of rice farmers in Pabuaran District, Sukabumi Regency, using a simple linear regression analysis approach. The simple linear model is used to isolate the direct relationship between external ecological factors (rainfall) and farm economic indicators. This quantitative research involved 30 rice farmer respondents selected through purposeful sampling method in the 2024/2025 Rendeng Planting Season. The results of simple linear regression analysis showed that rainfall intensity had a negative but insignificant effect on farmers' net income (p > 0.05). This result confirms the presence of omitted variable bias in simple linear modeling in agricultural economics. In reality, rice farmers' net income is multi-factored, which is dominantly controlled by internal farm variables such as land area mastery and input cost efficiency, rather than by a single shock of climate factors.